The Africans: A triple heritage : A Clash of cultures - Mazrui, Ali AlAmin (The Annnenberg/CPB Collection, 1986)
The effects of Islam and Westernization on African traditions and activities are depicted. A view of the continent from the inside looking out. Commentary by Ali A. Mazrui.